Pelatihan Penggunaan Aplikasi Lamikro Bagi Pelaku Usaha Mikro Di Kecamatan Kapuas Kabupaten Sanggau - bob Mustafa; Ariefanda Iqbal Perdana; Rahman Sastrawan; Nia Pratiwi; C. Hendreo; Ermina Ermina (Kapuas, 2021)
Micro and Small Enterprises (MSMEs) have proven resilient to the economic crisis that has hit Indonesia. MSMEs contribute significantly to the national economy by reducing the unemployment rate in Indonesia, whose presence is able to absorb labor. This Community Service Activity aims to provide an understanding of the importance of separating the owner's personal finances from his business finances. In addition, this training activity is also to provide knowledge and skills to micro-entrepreneurs in Kapuas District, Sanggau Regency in recording their business financial transactions through an Android-based application, namely LAMIKRO. The target audience in this service activity is micro-entrepreneurs in Kapuas District, Sanggau Regency. The implementation of PPM activities is carried out by coordinating with partners to identify problems with the target audience, compiling training materials, implementing training using the lecture method, tutorials, discussions, and simulations of using the Lamikro application, and evaluation in the form of pre-test and post-test. The results of this community service activity are according to the expected target, namely an increase in the knowledge and skills of micro-entrepreneurs using the LAMIKRO application in preparing their business financial reports in accordance with SAK EMKM. Keywords: UMKM, LAMIKRO